Implementation of the Culturally-Sensitive Independent Women's Class Program at the North Sumatra Provincial Agency for Women's Empowerment, Child Protection and Family Planning - M. Sufrizal Amri Harahap; Syafruddin Ritonga; Maksum Syahri Lubis (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Gender equality is one of the main goals of the Sustainable Development Goals (SDGs) launched by the United Nations. Women's empowerment is an important element in achieving equitable, sustainable, and inclusive development. North Sumatra Province still faces challenges in achieving the Gender Development Index (GDI) and Gender Empowerment Measure (GEM), which indicate that the role and position of women in development is not yet optimal. In an effort to address these issues, the North Sumatra Provincial Government, through the Office of Women's Empowerment, Child Protection, and Family Planning (DP3AKB), initiated the Independent and Cultured Women's Class Program (KELAPA MUDA). This study aims to analyze the implementation of the Independent and Cultured Women's Class Program and identify the factors that support and hinder its implementation. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The results of the study show that the implementation of the program has been carried out in accordance with the policy objectives, but has not been optimal due to limited resources, suboptimal coordination between organizations, and the influence of socio-cultural conditions in each region.